1978
DOI: 10.1042/bj1740621
|View full text |Cite
|
Sign up to set email alerts
|

The biochemical basis for the conjugation of bile acids with either glycine or taurine

Abstract: All animals, except for the placental mammals, conjugate their bile acids exclusively with taurine. However, in certain of the placental mammals, glycine conjugates are also found. The basis for the appearance of glycine conjugation among the placental mammals was investigated. The reaction of choloyl-CoA with glycine and taurine, as catalysed by the soluble fraction from guinea-pig liver, had a high affinity for taurine and a poor affinity for glycine. The predominant synthesis of glycine conjugates in the gu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
59
2

Year Published

1983
1983
2001
2001

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 145 publications
(64 citation statements)
references
References 15 publications
2
59
2
Order By: Relevance
“…), and the formation of taurine-or glycine-conjugated bile acids (1,4,5) is completed by these precesses. It has also been reported that in the mammalian liver a single enzyme, bile acid-Co A: amino acid N-acyltransferase, catalyzes the conjugation of bile acids both with taurine and glycine, and this enzyme has a higher affinity for taurine than glycine in the rat liver (6,7).…”
mentioning
confidence: 99%
“…), and the formation of taurine-or glycine-conjugated bile acids (1,4,5) is completed by these precesses. It has also been reported that in the mammalian liver a single enzyme, bile acid-Co A: amino acid N-acyltransferase, catalyzes the conjugation of bile acids both with taurine and glycine, and this enzyme has a higher affinity for taurine than glycine in the rat liver (6,7).…”
mentioning
confidence: 99%
“…The synthesis of taurine from methionine or cysteine via cysteic acid or hypotaurine has been reported in liver, brain, lung, and muscle tissues [9,23,25]. After being synthesized, the amino acid is not incorporated into protein but remains free in the intracellular cytosol [3], and is partly conjugated to form bile salts in the liver [31]. Excess taurine is excreted into the urine by the kidney [22].…”
mentioning
confidence: 99%
“…However, as information concerning the biological roles of taurine has accumulated, taurine has been illustrated to play many important physiological roles in animals, especially during their development. The possible functions of taurine currently proposed are as follows: conjugation of bile acids in the liver [31], improvement of fat absorption [1], maintenance of osmolarity [17], modulation of calcium levels [30], stabilization of membranes [12], antiarrhythmic activity in the heart [24], regulation of ion fluxes [7], and stimulation of sperm motility [20]. In the central nervous system, although the role of taurine is not well established, it has been proposed as a neurotransmitter or a neuromodulator [2].…”
mentioning
confidence: 99%
“…This indicates that the availability of large amounts of taurine did not decrease the percent of free bile acids despite the fact that the single transferase conjugation enzyme has a greater affinity for taurine than for glycine (41). Although the extent of sulfation increases with cholestasis (42), bile salt TAURINE AND BILE ACID MAXIMUM SECRETORY RATE 3 7 sulfotransferase activity has not been found to be inducible (43).…”
Section: Discussionmentioning
confidence: 99%